A cross-study transcriptional patient map of heart failure defines conserved multicellular coordination in cardiac remodeling - Lanzer, Jan David; Ramirez Flores, Ricardo O.; Liñares Blanco, José; Steier, Marco; Rangrez, Ashraf Yusuf; Frey, Norbert; Sáez Rodríguez, Julio (Nature Communications, 2025)
Impaired cardiac function in heart failure (HF) involves tissue remodeling through multicellular coordination. Although individual bulk and single-nucleus transcriptomics studies have offered insights, they have not been integrated to study conserved tissue-wide responses, limiting understanding of multicellular processes in cardiac remodeling necessary for therapeutic translation. Here, we integrate 25 studies of bulk and single-nucleus transcriptomics, spanning 1524 individuals, to define consensus multicellular programs associated with HF. These programs reveal conserved fibrotic, inflammatory, metabolic, and hypertrophic processes, with fibroblast activity consistently predicting cardiomyocyte stress. Our integration revealed that multicellular programs in HF are largely independent of tissue composition, and that fibroblast activation reflects a broad phenotypic shift rather than solely the emergence of discrete subtypes. Projecting external datasets onto these programs showed that clinical recovery aligns with reversion of disease-associated programs. This integrative analysis across studies establishes a public reference for the exploration of multicellular coordination in HF.